Transformative change through Payments for Ecosystem Services (PES): a conceptual framework and application to conservation agriculture in Malawi - Andrew Reid Bell; Tim G. Benton; Klaus Droppelmann; Lawrence Mapemba; Oliver Pierson; Patrick S. Ward (Global Sustainability, 2018)
A major challenge in addressing the loss of benefits and services provided by the natural environment is that it can be difficult to find ways for those who benefit from them to pay for their preservation. We examine one such context in Malawi, where erosion from soils disturbed by agriculture affects not only farmers’ incomes, but also damages aquatic habitat and inhibits the storage and hydropower potential of dams downstream. We demonstrate that payments from hydropower producers to farmers to maintain land cover and prevent erosion can have benefits for all parties involved.